Dutch Norming Study For 208 Color Drawings Depicting Transitive Events - Edwige Sijyeniyo; Robert J. Hartsuiker; Sarah Bernolet (University of Groningen Press, 2022)
We conducted a norming study amongst Dutch children (6-12 years) to investigate whether they would correctly interpret our set of 208 color drawings, developed for  longitudinal research on the production and comprehension of transitive sentences, if the transitive action on each drawing was described with an active or a  passive sentence. The children provided 93.02% correct answers to our pictures, which indicates that the pictures are clear in terms of how the transitive actions are displayed. There were several factors that contributed to an incorrect interpretation of a transitive action in a picture. (1) Pictures were more difficult to interpret when a passive  sentence was used to describe a transitive event compared to an active sentence; (2) children made more errors interpreting pictures when abstract verbs, such as  "inhalen" (to overtake) and "vervangen" (to replace), were used to describe a transitive event; (3) children had difficulty interpreting our pictures when particular verbs ("roepen" [to shout] and "volgen" [to follow]) were  presented in a passive sentence, while other verbs  ("blokkeren" [to block] and "inhalen") rendered more  correct answers when the transitive event was described  with a passive sentence; finally, (4) younger children  provided more incorrect answers to our pictures than older children, regardless of whether the transitive action in the picture was described with an active or a passive sentence. In particular, the younger children provided significantly more incorrect answers to pictures with the verb "groeten" (to greet) compared to the older children. Because our set contains many verb-noun combinations, the set is very useful to researchers who intend to investigate the  acquisition of transitive structures in children in a  longitudinal design, not only for studies with typically developing children, but also in studies with children who have a delay in their language development. Keywords: Norming study, picture set, transitive structures, L1 syntax acquisition.